Do FOMC Actions Speak Loudly? Evidence from Corporate Bond Credit Spreads - Javadi, Siamak; Nejadmalayeri, Ali; Krehbiel, Timothy L (Review of Finance, 2018)
Abstract We find that Federal Open Market Committee (FOMC) actions (especially rate cuts) narrowed corporate credit spreads during the pre-crisis period of 2002–07. During the 2008 crisis period, we find that both conventional cuts and quantitative easing decreased spreads. But FOMC inactions caused significant widening of spreads. The effects are especially large for speculative-grade and short-maturity bonds. Overall, the policy uncertainty during the crisis and macroeconomic theories during the pre-crisis period help to explain why FOMC announcements impacted credit spreads. The Fed’s actions targeted at promoting growth and/or providing systemic liquidity were especially noted by the corporate bond market.